Reconstruction of regional GDP in Colombia (1800-2015): A critical revision of sources and methods - Mejía, Javier (Sociedad y Economía, 2016)
This paper summarizes and analyzes the main sources and methods used in the reconstructionof regional GDPs in Colombia for the 19th and 20th centuries. In addition,it offers a general perspective of the field’s evolution in the coming years. It founds thatthe field is on a preliminary stage. The studies are few and most of them remain unpublished.Nevertheless, the growth rate of production, both of applications and sources,suggests a promising future. Additionally, it was identified that the research agendas forthe 19th and 20th centuries remain separated.